Location of national manufacturing in international context (the case of U.S.) - Nikolay Kurichev (European Regional Science Association (ERSA), 2014)
The case study of United States shows that global economic processes significantly influence the location of manufacturing. Analysis of multidimensional data covering 1860-2010 shows several stylized facts. Intensity of U.S. involvement in global economy by set of indicators is characterized by peaks in gold standard era (1870-1914) and under floating exchange rates (1970-2000s). Complex calculations show that spatial polarization of U.S. manufacturing declined in 1860-1890, rocketed by 1914, stabilized until 1940, then began to decline rapidly, and since 1980s has slightly grown again. Comparison of two datasets shows that increasing intensity of U.S. involvement in global economy leads with a certain time lag to the growth of spatial polarization. The less is interregional inequality in U.S. and the more integrated are national markets for goods and factors of production, the smaller are interregional shifts of manufacturing under changing global economic conditions. Growing opportunities of location decisions for U.S. companies in other countries leads to spatial polarization due to uneven efficiency in different industries and regions. The second group of stylized facts is the shift of U.S. manufacturing in last 50 years from cores of largest cities to small and medium MSAs. However, high-tech industries face the opposite trend. Simultaneously, level of agglomeration has been growing since mid-1980s. Rising international competition enhances selection of enterprises as TNCs optimize their operations globally and, because of strong link between productivity of an individual firm and concentration around its location, promotes agglomeration. Among components of agglomeration effect in industry, exchange of knowledge is the most important at county and postcode level, common pool of labor ? at MSA level, common pool of suppliers ? at the level of regions. Growing importance of innovations and their high concentration lead to the increasing level of agglomeration of U.S. manufacturing, reinforcing importance of local clusters and MSAs in comparison with industrial regions. Highly localized agglomeration effect in fast-growing sector of business services and high global demand for them lead to displacement of manufacturing from cores of large MSAs. Probably, in other large countries relationship of location of manufacturing and country's participation in global economy is close to American trends, taking into account level of economic development.
Keywords: R12; F60; 330; location of manufacturing; involvement in global economy; U.S.; spatial polarization; agglomeration effect